Peacekeeping in Sierra Leone The Story of UNAMSIL - Olonisakin, Funmi (A project of the International Peace Institute, 2022)
The inside story of how the UN mission in Sierra Leone was transformed from an embarrassing failure into what is now widely considered one of the most successful peacekeeping missions in UN history